PENGEMBANGAN PARIWISATA MELALUI INTEGRASI PERENCANAAN SUMBER DAYA MANUSIA DENGAN PERENCANAAN STRATEGIK PADA JEPARA OURLAND PARK: PENGEMBANGAN PARIWISATA MELALUI INTEGRASI PERENCANAAN SUMBER DAYA MANUSIA DENGAN PERENCANAAN STRATEGIK PADA JEPARA OURLAND PARK - Hanung Eka Atmaja; Shinta Ratnawati; Dian Marlina Verawati (STIMI Handayani Denpasar, 2018)
Human Resource Planning is defined as the anticipation of futurebusiness and environmental demand for a company and finds personal requestsarising from the condition. While Human Resource planning as a managementprocess to determine how the organization should move position. However, the linkbetween Human Resources planning and strategic management is often overlooked.Through this process the company is expected to have Human Resources in the rightamount, quality, place, time and generate long-term benefits for both individualsand organizations. The tourism sector is one of the main sectors of the Indonesiangovernment to generate foreign exchange, therefore the use, development,management and financing of tourist areas should receive serious attention from thegovernment by involving the role of government institutions, related stakeholdersand the participation of all levels of society.